Worldviews in Conflict - Allen, Tom (Maine Policy Review, 2014)
This article is an edited version of a lecture given in a lecture series, “Politics Then and Now, in Maine and the Nation,” presented by the Muskie School and Osher Lifelong Learning Institute at the University of Southern Maine in the fall of 2013. Speakers were asked to address the issue of political polarization and dysfunction, comparing how politics was played in the past with the current situation, and discussing what Maine can offer based on experiences here. Tom Allen analyzes the significance of conflicting worldviews in explaining the modern political climate in the U.S.
Keywords: Maine; politics; U.S. Congress; political polarization; American political parties; worldviews